PELATIHAN KEWIRAUSAHAAN BAGI GENERASI MUDA DAN IBU-IBU DESA WIDANG KABUPATEN TUBAN DALAM UPAYA PENGUATAN POTENSI DESA - Ellen Theresia Sihotang; Supriyati Supriyati; Dewi; Riski Aprillia Nita (Jurnal Abadimas Adi Buana, 2023)
The majority of people in Banjar, Tuban, have a lifelihood as farmers. The daily lives of residents depend on their husband’s income. The younger generation is not interested in the agricultural sector, while mothers only act as housewives, so there is no improvement in the community’s economy. Banjar village has the potential for productive human resources between the housewive and younger generation. Based on these conditions, the purpose of implementing this community service is to motivate and increase the entrepreneur spirit that can lift the village’s potential through the mothers and younger generation who are members of the Pembinaan Kesejahteraan Keluarga (PKK) and Karang Taruna. Through the training, community service acitivites are carried out by providing sewing training for a group of mothers, while dance training for children is managed by one of the dance studio in the village. Both activities received a good enthusiasm based on the results of the evaluation through questionnaires and direct observation. Creative innovation in sewing and dancing can increase the people’s economy. The sustainability of this acitivity is the use of social media as a part of technology to market the innovative of residents.